Sabrina P. Ramet, László Kürti, ur., Civic and Uncivic Values in Hungary: Value Transformation, Politics, and Religion (London; New York: Routledge, 2024), xiv + 239 str. (Časopis za suvremenu povijest, 2025)
Prikaz knjige